ATP-Induced Inflammasome Activation and Pyroptosis Is Regulated by AMP-Activated Protein Kinase in Macrophages - Zha, Qing-Bing; Wei, Hong-Xia; Li, Chen-Guang; Liang, Yi-Dan; Xu, Li-Hui; Bai, Wen-Jing; Pan, Hao; He, Xian-Hui; Ouyang, Dong-Yun (Frontiers in Immunology, 2016)
ATP is released by bacteria and host cells during bacterial infection as well as sterile tissue injury, acting as an inducer of inflammasome activation. Previous studies have shown that ATP treatment leads to AMP-activated protein kinase (AMPK) activation. However, it is unclear whether AMPK signaling has been involved in the regulation of ATP-induced inflammasome activation and subsequent pyroptosis. In this study, we aimed to investigate this issue in lipopolysaccharide-activated murine macrophages. Our results showed that AMPK signaling was activated in murine macrophages upon ATP treatment, which was accompanied by inflammasome activation and pyroptosis as evidenced by rapid cell membrane rupture as well as mature interleukin (IL)-1β and active caspase-1p10 release. The ATP-induced inflammasome activation and pyroptosis were markedly suppressed by an AMPK inhibitor compound C or small interfering RNA-mediated knockdown of AMPKα, but could be greatly enhanced by metformin (a well-known AMPK agonist). Importantly, metformin administration increased the mortality of mice with bacterial sepsis, which was likely because metformin treatment enhanced the systemic inflammasome activation as indicated by elevated serum and hepatic IL-1β levels. Collectively, these data indicated that the AMPK signaling positively regulated ATP-induced inflammasome activation and pyroptosis in macrophages, highlighting the possibility of AMPK-targeting therapies for inflammatory diseases involving inflammasome activation.